Thermogravimetric Analysis of 2,6 Diaminopyridine Substituted Polymers Using Green Conditions and Conventional Method (Indian Journal of Chemistry (IJC), 2024)
Polyamide were synthesised by a modified phosphorylation method using 2,6 diaminopyridine with diacids such as  citraconic acid, succinic acid and phthalic acid was carried out with  NMP/Pyridine mixture containing 4%  LiCl using the following conditions: Higashi to increase  viscosity and thermal stability, reported by the authors. In the present study we carried out the synthesis  under green conditions ionic liquid and microwave combined with ionic liquid and the results compared. Thermogravimetric analysis of  synthesized polymers was performed in the temperature range 30 to 900°C. Thermogravimetric data were used to calculate activation energies and compared with other integral and differential methods like Friedmann. Freeman-Caroll, Coats-Redfern, Chang, Sharp Wentworth . Kinetic parameters - Gibb’s free energy, entropy and enthalpy were determined for all polyamides synthesized using microwave assisted ionic liquid method employing Coats-Redfern method. Regression analysis was carried out for all the three polyamides for all the stages of decomposition which involves seven different kinetic models. The limiting oxygen index was calculated and the fire-retardant properties were noted. This result is compared with all methods.